2016
DOI: 10.1007/s00431-016-2696-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of ADAM17 are implicated in the pathological process of Kawasaki disease and secondary coronary artery lesions via the TGF-β/SMAD3 signaling pathway

Abstract: • The transforming growth factor (TGF)-β/SMAD3 signaling pathway greatly influences susceptibility to Kawasaki disease (KD) and secondary coronary artery lesions (CALs) and/or the treatment response of intravenous immunoglobulin. • A disintegrin and metalloprotease 17 (ADAM17) effectively reduces TGF-β signaling by cleaving TGF-β receptor type-1, while ADAM17 genetic variants modify human vascular pathology by differentially regulating this signaling although it is unknown whether ADAM17 contributes to KD phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Many genetic researches demonstrated that several functional single nucleotide polymorphisms (SNPs) within the ADAM17 gene are associated with differences in immune inflammatory response and disease outcomes [25][26][27][28][29][30][31]. To the best of our knowledge, this present study was the first to analyze the clinical relevance of the five polymorphisms (rs55790676, rs12692386, rs11684747, rs1524668 and rs11689958) within the promoter region of ADAM17 to the susceptibility and progression of sepsis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many genetic researches demonstrated that several functional single nucleotide polymorphisms (SNPs) within the ADAM17 gene are associated with differences in immune inflammatory response and disease outcomes [25][26][27][28][29][30][31]. To the best of our knowledge, this present study was the first to analyze the clinical relevance of the five polymorphisms (rs55790676, rs12692386, rs11684747, rs1524668 and rs11689958) within the promoter region of ADAM17 to the susceptibility and progression of sepsis.…”
Section: Discussionmentioning
confidence: 96%
“…Several genetic variations of ADAM17 have been demonstrated to be involved in various inflammation-related diseases, such as Kawasaki disease, obesity, Alzheimer's disease and ischemic stroke [25][26][27][28]. A recent study has demonstrated that two functional genetic variations of ADAM17, C-154A and Ser747Leu, contribute to high serum concentration of TNF-α and increased susceptibility to cardiovascular death [29].…”
Section: Introductionmentioning
confidence: 99%
“…set 2)276/282xOnouchi et al [92] (Indep. set 3)267/752xOnouchi et al [95]546/947Yes ( ITPKC )Yes ( ITPKC ) i Yes ( ITPKC ) i ChinesePeng et al [97]223/318Yes ( ITPKC )Yes (ITPKC)NoKhor et al [61]130/568Yes ( ITPKC )xxTaiwaneseChi et al [18]385 (of which 158 trios)/1158NoNoxLin et al [73]280/492Yes ( ITPKC )NoxKuo et al [71]341/1190Yes ( ITPKC )Yes ( ITPKC ) j NoAbove-mentioned studies combined999/2781Yes ( ITPKC )xxKuo et al [68]381/569No k Yes ( ITPKC )xKhor et al [61]438/446Yes ( ITPKC )xxEuropeanKhor et al [61] (GWAS)405/6252 (10)Yes ( ITPKC )xxKhor et al [61] (Replication) 605 trios, 139 siblings l xxUSOnouchi et al [92]209 triosYes ( ITPKC )Yes ( ITPKC )Yes ( ITPKC )TGF-β pathwayJapaneseCho et al [20]105/303Yes ( SMAD5 )NoxHan ChinesePeng et al [98]392/421Yes ( TGFB2 , SMAD3 , ADAM17 )Yes ( TGFB2 )NoTaiwaneseKuo et al [70]381/569Yes ( SMAD3 )NoNoKoreanChoi et al [21]105/500Yes ( TGFBR2 )Yes ( TGFBR2 )xEuropean descent…”
Section: Geneticsmentioning
confidence: 99%
“…and activated by transforming growth factor (TGF)-β signaling pathway. TGF-β pathway is involved in in ammation and tissue remodeling mediated by endothelial cells, and immune activation, which support the importance of TGF-βpathway in KD occurrence and outcomes [15,16].CD34 positive cells with enhanced adhesive and homing properties facilitates immune cells homing to the in ammatory sites and mediates in ammatory and immune responses [17].CXCL1, as the chemokine ligand, presents on endothelial surface and mediates immune responses by recruitment of neutrophils and monocytes [18,19].APLN(apelin) is a vasoactive peptide and an endogenous ligand for APJ receptors. APLN/APJ receptor system plays a vital role in regulation of vascular function, including vascular tone, angiogenesis, proliferation, and permeability [20,21].In addition, APLN/APJ system also mediates the anti-in ammatory effects of 1,25(OH)2D3 by reduction of pro-in ammatory mediators and adhesion molecules in LPS-stimulated macrophages [22].…”
Section: Discussionmentioning
confidence: 69%